High MMP-11 expression associated with low CD8+ T cells decreases the survival rate in patients with breast cancer. - Hyung Suk Kim; Min Gyu Kim; Kyueng-Whan Min; Un Suk Jung; Dong-Hoon Kim (PLoS ONE)
Matrix metalloproteinase-11 (MMP-11) promote cancer invasion and metastasis through degrading the extracellular matrix. Protein degradation by MMP-11 in tumor cells may progressively suppress cancer surveillance activities with blocking immune response in breast cancer. The aim of study is to analyze clinicopathological parameters, molecular interactions and anticancer immune response in patients with MMP-11 expression and to provide candidate target drugs. We investigated the clinicopathologic parameters, specific gene sets, tumor antigenicity, and immunologic relevance according to MMP-11 expression in 226 and 776 breast cancer patients from the Hanyang University Guri Hospital (HUGH) cohort and The Cancer Genome Atlas (TCGA) data, respectively. We analyzed pathway networks and in vitro drug response. High MMP-11 expression was associated with worse survival rate in breast cancer from HUGH cohort and TCGA data (all p < 0.05). In analysis of immunologic gene sets, high MMP-11 expression was related to low immune response such as CD8+T cell, CD4+T cell and B cell. In silico cytometry, there was a decrease of cancer testis antigen and low tumor infiltrating lymphocyte in patient with high MMP-11 expression: activated dendritic cell, CD8+T cell, CD4+ memory T cell, and memory B cell. In pathway networks, MMP-11 was linked to the pathways including low immune response, response to growth hormone and catabolic process. We found that pictilisib and AZ960 effectively inhibited the breast cancer cell lines with high MMP-11 expression. Strategies making use of MMP-11-related hub genes could contribute to better clinical management/research for patients with breast cancer.